2018
DOI: 10.1038/s41598-018-26114-z
|View full text |Cite
|
Sign up to set email alerts
|

Malonylation of histone H2A at lysine 119 inhibits Bub1-dependent H2A phosphorylation and chromosomal localization of shugoshin proteins

Abstract: Post-translational modifications of histones, such as acetylation and phosphorylation, are highly conserved in eukaryotes and their combination enables precise regulation of many cellular functions. Recent studies using mass spectrometry have revealed various non-acetyl acylations in histones, including malonylation and succinylation, which change the positive charge of lysine into a negative one. However, the molecular function of histone malonylation or succinylation is poorly understood. Here, we discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…7 ). Interestingly, a recent report showed that malonylation on H2A in yeasts also prevented Bub1-mediated phosphorylation and Sgo1 accumulation 45 . Thus, histone modifications at the H2A-K118 would affect the Bub1-mediated phosphorylation in both humans and yeasts but they may use different histone modifications.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Interestingly, a recent report showed that malonylation on H2A in yeasts also prevented Bub1-mediated phosphorylation and Sgo1 accumulation 45 . Thus, histone modifications at the H2A-K118 would affect the Bub1-mediated phosphorylation in both humans and yeasts but they may use different histone modifications.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of lower eukaryotes is that it is relatively simple to replace all endogenous histones with the mutated ones. For example, H2BK37E (as a K37succ mimic), H2AK119E (as a K119mal mimic), and H4K91E (as a H4K91glu mimic) mutant yeast strains were used to investigate chromatin structure changes in vivo and complemented existing in vitro data nicely (Ishiguro et al, 2018;Jing et al, 2018;Bao et al, 2019). Nevertheless, no mimic can entirely resemble the actual modification and close structural similarity of some short-chain lysine acylations such as Kac, Kpr, or Kbu makes it difficult to mimic acylations specifically Zorro Shahidian et al, 2021).…”
Section: Impact Of Histone Acylations On Chromatin Structurementioning
confidence: 99%
“…Further studies indicate that crotonylation plays a role in maintaining the pluripotent state in mouse embryonic stem cells [96], assists histone replacement during spermatogenesis [87] and can reverse HIV latency [97], potentially providing a therapeutic opportunity. One recent study has suggested that malonylation of yeast H2A may lead to a chromosome segregation defect [98]. Hypersuccinylation, achieved by both the depletion of SIRT7 and succinate dehydrogenase, results in defects in DNA repair [99,100].…”
Section: Physiological Roles Of Diverse Acylationsmentioning
confidence: 99%